Heterogeneous Reaction of CaCO3 With NO2 at Different Relative Humidities: Kinetics, Mechanisms, and Impacts on Aerosol Hygroscopicity. Issue 11 (1st June 2021) - Jia, Xiaohong; Gu, Wenjun; Peng, Chao; Li, Rui; Chen, Lanxiadi; Wang, Hongli; Wang, Haichao; Wang, Xinming; Tang, Mingjin
Abstract: Heterogeneous reaction of NO2 with CaCO3, an abundant and reactive component in mineral dust aerosol, was investigated in this work at different relative humidifies (RH, up to 80%), using a fixed‐bed reactor. Ion chromatograph and a vapor sorption analyzer were employed to measure changes in particulate nitrate and water with reaction time (up to 24 h). When NO2 concentration was ∼10 ppmv (∼2.5 × 10 14 molecule cm −3 ), CaCO3 showed very low reactivity toward NO2 at <1% RH, and γ (NO2 ) was estimated to be <2 × 10 −8 ; consequently, no significant change in hygroscopicity of CaCO3 particles was observed after reaction with NO2 for 24 h at <1% RH, as the amount of nitrate formed was very limited. Heterogeneous reactivity was significantly enhanced at elevated RH (20%–80%), and during the reaction CaCO3 was covered with a deliquesced layer resulting from water uptake by formed nitrate; in addition, the average γ (NO2 ) was determined to be (1.21 ± 0.45) × 10 −7, independent of RH (20%–80%) and reaction time (3–24 h). After reaction with 10 ppmv NO2 for 24 h at elevated RH (20%–80%), the mass of particulate water associated with reacted CaCO3 at 90% RH was equal to ∼45% of the mass of unreacted CaCO3, suggesting that heterogeneous reaction of CaCO3 with NO2 at 20%–80% RH could substantially increase its hygroscopicity. Overall, our laboratory study suggested that heterogeneous reaction with NO2 may significantly impact composition and hygroscopicity of CaCO3 particles. Key Points: Heterogeneous reactivity of CaCO3 toward NO2 was limited at <1% relative humidity (RH), with uptake coefficient estimated to be <2 × 10 −8 This reaction was enhanced at elevated RH, and average uptake coefficients were measured to be ∼1.2 × 10 −7 at 20%–80% RH Heterogeneous reaction with NO2 significantly increased hygroscopicity of CaCO3 particles